2023
DOI: 10.1001/jamasurg.2023.1035
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Postoperative Overnight High-Acuity Care in Medium-Risk Patients Undergoing Elective and Unplanned Noncardiac Surgery

Abstract: ImportancePostoperative complications are increasing, risking patients’ health and health care sustainability. High-acuity postoperative units may benefit outcomes, but existing data are very limited.ObjectiveTo evaluate whether a new high-acuity postoperative unit, advanced recovery room care (ARRC), reduces complications and health care utilization compared with usual ward care (UC).Design, Setting, and ParticipantsIn this observational cohort study, adults who were undergoing noncardiac surgery at a single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Alongside advances in intra-operative and postoperative care [34], there is an urgent need to examine all potential means of modifying risk pre-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside advances in intra-operative and postoperative care [34], there is an urgent need to examine all potential means of modifying risk pre-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor We read with great interest the article by Ludbrook et al, which reported on the potential benefits of a new postoperative overnight high-acuity care unit (advanced recovery room care [ARRC]) with a decreased incidence of subsequent medical emergency response–level complications and increased days at home at 30 days. However, we have concerns regarding inconsistent definitions and potential confounding factors in this study.…”
mentioning
confidence: 99%
“…Second, we noticed a discrepancy in the range of 30-day mortality according to American College of Surgeons National Surgical and Quality Improvement Program risk score predictions presented in Table 1 . If the authors used a range of 0.7% to 5% as an inclusion criterion for this study, it is puzzling to observe values exceeding this range in the usual care group (0.7%-5.4%) and the ARRC group (0.2%-5.9%) for all patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Reply We thank Hsu and colleagues for their Letter to the Editor and detailed evaluation of our article . They raise 3 interesting points.…”
mentioning
confidence: 99%